Effectiveness and Cost‑Effectiveness Of Integrating the Management of Depression into Routine HIV Care in Uganda (the HIV + D trial): A protocol for a cluster‑randomised trial - Kinyanda, Eugene; Kyohangirwe, Leticia; Mpango, Richard S.; Tusiime, Christine; Ssebunnya, Joshua; Katumba, Kenneth; Tenywa, Patrick; Mugisha, James; Sentongo, Hafsa; Akena, Dickens; Muhwezi, Wilson; Kaleebu, Pontiano; et al. (International journal of mental health systems, 2021)
An estimated 8–30 % of people living with HIV (PLWH) have depressive disorders (DD) in sub-Saharan Africa. Of these, the majority are untreated in most of HIV care services. There is evidence from low- and middle- income countries of the effectiveness of both psychological treatments and antidepressant medication for the treatment of DD among PLWH, but no evidence on how these can be integrated into routine HIV care. This protocol describes a cluster-randomised trial to evaluate the effectiveness and cost-effectiveness of the HIV + D model for the integration of a collaborative stepped care intervention for DD into routine HIV care, which we have developed and piloted in Uganda.Forty public health care facilities that provide HIV care in Kalungu, Masaka and Wakiso Districts will be randomly selected to participate in the trial. Each facility will recruit 10–30 eligible PLWH with DD and the total sample size will be 1200. The clusters will be randomised 1:1 to receive Enhanced Usual Care alone (EUC, i.e. HIV clinicians trained in Mental Health Gap Action Programme including guidelines on when and where to refer patients for psychiatric care) or EUC plus HIV + D (psychoeducation, Behavioural Activation, antidepressant medication and referral to a supervising mental health worker, delivered in a collaborative care stepwise approach). Eligibility criteria are PLWH attending the clinic, aged ≥ 18 years who screen positive on a depression screening questionnaire (Patient Health Questionnaire, PHQ-9 ≥ 10). The primary outcome is the mean depressive disorder symptom severity scores (assessed using the PHQ-9) at 3 months’ post-randomisation, with secondary mental health, disability, HIV and economic outcomes measured at 3 and 12 months. The cost-effectiveness of EUC with HIV + D will be assessed from both the health system and the societal perspectives by collecting health system, patient and productivity costs and mean DD severity scores at 3 months, additional to health and non-health related quality of life measures (EQ-5D-5 L and OxCAP-MH).The study findings will inform policy makers and practitioners on the cost-effectiveness of a stepped care approach to integrate depression management in routine care for PLWH in low-resource settings.
Keywords: Cluster randomised trial, Depression, Routine HIV care, Public health care facilities